The clinical spectrum of central neurocytomas ranges from benign to leptomeningeal disseminating disease: a single institutional surgical series of 33 patients - Yaşar, A. Harun; Erşen-Danyeli, Ayça; Bozkurt, Baran; Usseli, M. İmre; Güdük, Mustafa; Özduman, Koray; Pamir, M. Necmettin (Frontiers in Surgery, 2025)
BackgroundCentral neurocytomas (CN) are rare neuroepithelial neoplasms primarily found in the lateral ventricles. While generally considered benign, their clinical behavior varies, with some cases displaying atypical features associated with increased recurrence risk.Material and methodsThis is a retrospective analysis of 33 adult CN patients that were operated and followed over a 25-year period by a single surgeon. Demographic (age, gender), anatomical (localization), histopathological (atypical histology, Ki67 index, p75NTR expression), extent of resection (GTR vs. STR), adjuvant treatments (radiotherapy and radiosurgery) were analyzed as potential prognostic factors.ResultsGross total resection (GTR) was associated with favorable outcomes, with adjuvant radiotherapy effective after subtotal resection (STR). Notably, a subset of aCN cases exhibited p75NTR immunopositivity, suggesting its potential as a prognostic marker for aggressive behavior. Leptomeningeal dissemination was rare but observed in one case.ConclusionCN cases demonstrate clinical heterogeneity, emphasizing the importance of tailored management. Close follow-up is crucial, particularly in atypical cases, to optimize patient outcomes. GTR remains the goal in surgery, while p75NTR expression may serve as a prognostic indicator but further research is needed to validate p75NTR as a prognostic factor in CN.